INVESTIGASI PENGARUH JENIS MIKROORGANISME LOKAL PADA KUALITAS POC YANG DIHASILKAN DARI POME - Setyowati, Sekar Ayu; Fitriyana, Fitriyana; Aisyah, Cici Nur (Universitas 17 Agustus 1945 Samarinda, 2025)
Liquid organic fertilizer primarily consists of components derived from fermented animal or plant materials. Palm Oil Mill Effluent (POME) is an organic waste comprising water, oil, and organic solids. Empty Fruit bunches (EFB) of oil palm serve as a source of organic material rich in nitrogen (N), phosphorus (P), potassium (K), and magnesium (Mg). The aim of this research is to determine the impact of local microorganisms in steamed rice and EFB on the production of liquid organic fertilizer by incorporating EFB fibers and molasses, followed by a 13-day fermentation period. The experimental design utilized MOL derived from steamed rice and EFB bioactivators, with MOL volumes varying at 40, 60, 80, 100, and 120 mL. The results indicated that the addition of MOL positively influenced both nitrogen content and pH levels, which increased with higher MOL volumes. In contrast, the effect of MOL on phosphorus and potassium content displayed a stagnant trend. The highest nitrogen 0.25 and phosphorus 0.03% (w/v) concentrations were observed in the liquid organic fertilizer produced with 120 mL of EFB-derived MOL. The optimal potassium content 0.48% (w/v) was achieved with 80 mL of EFB-derived MOL. The most favorable pH levels were recorded at MOL volumes of 40 and 60 mL, measuring 7.28 and 7.49.